Nonlinear filtering, interpolation and extrapolation in stochastic systems under continuous and discrete observations with memory; IFAC Proceedings Volumes; Vol. 2 - Dyomin N. S. Nikolas (2004, 2004)
В фонде НТБ ТПУ отсутствует